A Numerical Study on the Crashworthiness of Corrugated Conical Tubes with Small Semi-Apical Angles and Their Influence Mechanism - Yiheng Song; Qinyu Lin; Jinxiang Chen; Tidong Zhao (Biomimetics)
To develop a new type of biomimetic single-cell and multi-cell energy-absorbing box (tube) featuring conical tubes at the intersection of cell walls, it is necessary to address the issue of large bottom-space requirements in current conical energy-absorbing tubes with superior crashworthiness due to their large semi-apical angles. This study proposes adding corrugations to conical tubes with small semi-apical angles and modifying the bottom by replacing the last one or two inclined corrugations with vertical ones. Finite element simulation results show that, compared to conventional conical tubes, adding corrugations reduces the optimal semi-apical angle of conical tubes by 5°, with the optimal range being 5–10°. Furthermore, the modification method of replacing inclined corrugations with vertical ones effectively mitigates the challenges of increasing peak crushing force and large end-peak crushing force as the semi-apical angle increases. This structural optimization lays a foundation for the development of new biomimetic single-cell and multi-cell energy-absorbing boxes (tubes) incorporating conical tubes.